The vulnerable seagrass Halophila beccarii Aschers. (Hydrocharitaceae) from Malaysia - Zakaria, Muta Harah; Syed, Nurul Nur Farahin; Bujang, Japar Sidik (Frontiers in Conservation Science, 2025)
Halophila beccarii Aschers. is a small, vulnerable seagrass species found throughout the Indo-West Pacific. In Malaysia, its distribution is highly fragmented and faces increasing threats from human activities and natural disturbances. Although it can tolerate various ecological conditions, its limited and scattered range raises significant conservation concerns. Long-term observations and monitoring were conducted from 1996 to 2025 at numerous coastal and estuarine sites within Peninsular Malaysia, Sabah, and Sarawak. Historical data and recent field surveys were combined to assess changes in distribution, population status, and habitat conditions. Halophila beccarii, once considered rare, was found at 15 locations across various intertidal habitats, ranging from freshwater to the brackish waters of mangrove river systems, shallow coastal lagoons, marine coastal areas, and subtidal shoals. It is commonly observed at depths of 1.0 to 2.0 meters and rarely exceeds 3.0 meters during high tide. The species thrives in temperatures from 25 to 38°C and salinity levels from 0 to 32 psu. Scattered patches or monospecific meadows of H. beccarii often occur alongside other seagrasses, such as Halodule pinifolia, macroalgae, seaside grasses, or mangroves, on substrates including sand, silty sand, loam, and calcareous mud. Declines are driven by reclamation, dredging, sand mining, sedimentation, monsoonal flooding, and coastal erosion. Disturbed habitats often shift to dominance by H. pinifolia, a more resilient species. These findings highlight H. beccarii’s vulnerability despite its ecological adaptability, reinforcing its current IUCN “Vulnerable” status and emphasizing the need for targeted conservation, seed bank protection, and adaptive monitoring strategies.